Depression and psychosocial factors in Turkish women with fibromyalgia syndrome - (:unkn) unknown (My University, 2005)
AIM: The aim of this study was to evaluate the demographic qualifications, frequency of depression, degree of pain, and the correlations between these factors in Turkish women with fibromyalgia syndrome (FS). METHODS: Fifty-three women with FS and 54 healthy women were included in the study. The visual analogue scale (VAS) was applied to evaluate the degree of pain and Beck depression inventory (BDI) for depression. RESULTS: Mean age of the FS and the healthy women groups was 42.6+/-9.6 (21-63) and 39.4+/-13.2 (24-60) years respectively; which were statistically similar (P>0.05). Of the patients, 69.8% were married, and the mean years of education was 8.7+/-4.8 years. Marriage among relatives was found in 18.4% of the patients. The mean VAS score of the patients was 7.2+/-1.7 cm with the mean duration of pain 5+/-4.6 years. Mean BDI scores of FS patients and the healthy group were 15.7+/-8.7 and 10.2+/-5.5 respectively; the difference between the 2 groups was statistically significant (P<0.05). According to the BDI scores, 90% of FS patients were classified as depressed; among them, 50% had minor, 38% moderate, and 2% severe depression. FS patients who were married to a relative had higher scores of BDI (r=0.414, P=0.013). There was negative correlation between BDI score and patients' total year of education (r=-0.295, P=0.037); and the husband's education level (r=-0.367, P=0.030). According to BDI, the c2 test revealed significant depression in patients with sleep-disorders (P=0.009). CONCLUSIONS: We found a significant degree of depression in Turkish female FS patients. This situation is found to be correlated with the education level of both patient and husband; marital status, and sleep-disorder; it is suggested that these factors should be taken into consideration in the diagnosis, treatment and follow-up of FS patients.
Keywords: Adult; Female; Humans; Middle Aged; Turkey; Fibromyalgia; Socioeconomic Factors; Depression; Educational Status; Pain Measurement; Personality Inventory; Marital Status